2010
DOI: 10.2215/cjn.05850809
|View full text |Cite
|
Sign up to set email alerts
|

Serum Potassium and Outcomes in CKD

Abstract: Background and objectives:The relationship between serum potassium (S K ) and mortality in chronic kidney disease (CKD) has not been systematically investigated.Design, setting, participants, & measurements: We examined the predictors and mortality association of S K in the Renal Research Institute CKD Study cohort, wherein 820 patients with CKD were prospectively followed at four US centers for an average of 2.6 years. Predictors of S K were investigated using linear and repeated measures regression models. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
160
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(182 citation statements)
references
References 39 publications
16
160
1
5
Order By: Relevance
“…Current Kidney Disease Outcomes Quality Initiative guidelines recommend that base be given when serum bicarbonate levels are ,22 mEq/L and to maintain a level $22 mEq/L, and Kidney Disease Improving Global Outcomes guidelines also recommend administering base when serum bicarbonate is ,22 mEq/L to maintain the value within the normal range of 22-29 mEq/L (25-29). Use of guideline-recommended alkali therapies and/or increased intake of fruit and vegetables reflects current clinical practice; however, these interventions have the potential to introduce large amounts of sodium or potassium to patients with CKD who often have hypertension, fluid overload, and hyperkalemia (28)(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…Current Kidney Disease Outcomes Quality Initiative guidelines recommend that base be given when serum bicarbonate levels are ,22 mEq/L and to maintain a level $22 mEq/L, and Kidney Disease Improving Global Outcomes guidelines also recommend administering base when serum bicarbonate is ,22 mEq/L to maintain the value within the normal range of 22-29 mEq/L (25-29). Use of guideline-recommended alkali therapies and/or increased intake of fruit and vegetables reflects current clinical practice; however, these interventions have the potential to introduce large amounts of sodium or potassium to patients with CKD who often have hypertension, fluid overload, and hyperkalemia (28)(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, extremes of serum K + were associated with greater rates of discontinuation of RAAS blockers. Prior studies have reported the prevalence of hyperkalemia and hypokalemia (9)(10)(11). However, the generalizability of these studies to the CKD population is limited by small sample sizes and a disproportionate representation of patients with very advanced CKD (10,11); the largest of these studies focused on clinical trial participants with concomitant heart failure, further limiting generalizability (11).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported the prevalence of hyperkalemia and hypokalemia (9)(10)(11). However, the generalizability of these studies to the CKD population is limited by small sample sizes and a disproportionate representation of patients with very advanced CKD (10,11); the largest of these studies focused on clinical trial participants with concomitant heart failure, further limiting generalizability (11). In another study, a U-shaped association between serum K + and mortality was observed among patients with CKD who had a mean eGFR,25 ml/min per 1.73 m 2 (9); however, risk estimates for higher K + categories did not achieve statistical significance, possibly because of a small sample size: Only 65 hyperkalemic patients were included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum potassium >5.0 mmol/L was associated with increased mortality in non-dialysis dependent CKD patients [28]. A secondary analysis of the Renal Research Institute study CKD cohort also showed an increased risk of the composite of death or cardiovascular events requiring hospitalization but no increase in overall mortality with serum potassium >5.5 mmol/L [29]. These studies are limited to CKD subjects only.…”
Section: Archives Of Medicine Issn 1989-5216mentioning
confidence: 85%